2023
DOI: 10.1002/imhj.22035
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of parenting styles, cultural values, and infant development in a sample of Latin American immigrants in Canada

Abstract: The objective of the current research was to investigate the relationship between parenting style, culture, and infant development in a sample of Latin American mother-infant dyads in Toronto, Canada. We examined associations between mothers' self-reported parenting style and infant cognitive and socioemotional development, which we compared to results from mothers belonging to two other Canadian immigrant populations. We further examined whether specific cultural correlates, including affiliation with traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Therefore, in some studies, parents in collectivist cultures tend to promote interdependence in their children and have higher levels of authoritarian parenting styles, in contrast with individualistic cultures that tend to emphasize independence (Lansford et al, 2021;Pinquart & Kauser, 2018;Posada et al, 2002;Simaes et al, 2022). Research has demonstrated the importance of parenting (i.e., attitudes, rules, and regulations toward nurturing; Baumrind, 1966) and the home environment to children's development of EFs in the first 12 years, but this understanding is limited to work primarily from individualistic cultures (e.g., Bernier et al, 2010Bernier et al, , 2012Blum & Ribner, 2022;Hamel et al, 2023).…”
Section: The Cultural Context Of Latin American Countriesmentioning
confidence: 99%
“…Therefore, in some studies, parents in collectivist cultures tend to promote interdependence in their children and have higher levels of authoritarian parenting styles, in contrast with individualistic cultures that tend to emphasize independence (Lansford et al, 2021;Pinquart & Kauser, 2018;Posada et al, 2002;Simaes et al, 2022). Research has demonstrated the importance of parenting (i.e., attitudes, rules, and regulations toward nurturing; Baumrind, 1966) and the home environment to children's development of EFs in the first 12 years, but this understanding is limited to work primarily from individualistic cultures (e.g., Bernier et al, 2010Bernier et al, , 2012Blum & Ribner, 2022;Hamel et al, 2023).…”
Section: The Cultural Context Of Latin American Countriesmentioning
confidence: 99%
“…We used the Parenting Styles and Dimensions Questionnaire (PSDQ) [101][102][103] which is known as one of the few psychometrically robust scales measuring parenting practices [104] and has also been used in multiple different cultural groups [105]. This choice is justified by the idea that parents can engage in practices that align with any parenting style at different moments to different degrees [106].…”
Section: The Current Studymentioning
confidence: 99%